FAMILY-MARRIAGE RELATIONS AND ETHNIC TRADITIONS IN WEDDING CEREMONIES OF SURKHAN OASIS GYPSIES - Rozieva Mashkhura Abdimuminovna (Journals Park Publishing, 2022)
This article talks about family-marriage values, which have an important place in the ethnocultural life of Gypsies living in Surkhandarya region. Based on ethnographic data, field research, the author studied the specific aspects of Gypsy weddings of Surkhan oasis based on available scientific literature.